ÐžÑ†ÐµÐ½ÐºÐ° Ñ‚ÐµÑ€Ð°Ð¿ÐµÐ²Ñ‚Ð¸Ñ‡ÐµÑÐºÐ¾Ð³Ð¾ Ð¿Ð¾Ñ‚ÐµÐ½Ñ†Ð¸Ð°Ð»Ð° ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº Ñ„ÐµÑ‚Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ Ð² Ð¼Ð¾Ð´ÐµÐ»Ð¸ ÑÐºÑÐ¿ÐµÑ€Ð¸Ð¼ÐµÐ½Ñ‚Ð°Ð»ÑŒÐ½Ð¾Ð³Ð¾ Ð°ÑƒÑ‚Ð¾Ð¸Ð¼Ð¼ÑƒÐ½Ð½Ð¾Ð³Ð¾ Ñ‚Ð¸Ñ€ÐµÐ¾Ð¸Ð´Ð¸Ñ‚Ð° - Gladkikh, D. P.; Goltsev, A. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2009)
In experimental model of autoimmune thyroiditis a therapeutic efficiency of native and cryopreserved fetal liver cells (FLCs) was demonstrated. The advantages and possible mechanisms of therapeutic effect of fetoplacental complex preparations and FLCs, in particular, were envisaged.